State of the art in burn care: principles and advances in surgical management - Toledo, Yosuany Roberto Gómez; Gaviño, Urías Zavala (International Surgery Journal, 2026)
Burn injuries remain a major global health challenge, associated with high morbidity, mortality, and long-term disability, particularly in low- and middle-income countries. Over the past decades, burn care has evolved into a multidisciplinary field that integrates early resuscitation, surgical intervention, intensive care, rehabilitation, and long-term reconstruction. Accurate assessment of burn depth and total body surface area, prompt fluid resuscitation, infection prevention, and timely surgical decision-making are fundamental to improving outcomes. Early excision and wound closure, most commonly achieved through split-thickness skin grafting, remain the cornerstone of surgical management for deep burns, while alternative strategies such as dermal substitutes, temporary biological dressings, and bioengineered skin have expanded options for patients with extensive injuries or limited donor sites. Long-term care focuses on the prevention and treatment of scarring and contractures through staged reconstruction and structured rehabilitation. This state-of-the-art review summarizes current principles and advances in burn surgical management, emphasizing individualized, multidisciplinary, and resource-sensitive approaches.